Nanohybrids of silver particles on clay platelets delaminate Pseudomonas biofilms. (July 2014) - Tseng, Li-Ping; Juan, Chih-Yin; Lin, Shiun-Long; Doran, Michael R; Lin, Jiang-Jen; Hsu, Shan-Hui; Liao, Jiunn-Wang; Shen, Ching-I; Su, Hong-Lin
Aim: To evaluate the effectiveness of novel nanohybrids, composed of silver nanoparticles and nanoscale silicate platelets, to clear Pseudomonas aeruginosa biofilms.Materials & methods: The nanohybrids were manufactured from an in situ reduction of silver salts in the silicate platelet dispersion, and then applied to biofilms in vitro and in vivo .Results: In reference to the biocidal effects of gentamycin, the nanohybrids mitigated the spreading of the biofilms, and initiated robust cell death and exfoliation from the superficial layers of the biofilms in vitro . In vivo, the nanohybrids exhibited significant therapeutic effects by eliminating established biofilms from infected corneas and promoting the recovery of corneal integrity.Conclusion: All of the evaluations indicate the high potency of the newly developed silver nanoparticle/nanoscale silicate platelet nanohybrids for eliminating biofilms. Original submitted 6 June 2012; revised submitted 13 February 2013